اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻛﻌﺎﻤل ﻤﻨﺒﺊ ﺒﻨﺸوء اﻟﺸﺨﺼﯿﺘﯿن اﻟﻨرﺠﺴﯿﺔ واﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس - ﺨﻠﯿﻔﺔ ﻤﺒﺎرﻛﺔ (جامعة البليدة 2؛ كلية العلوم الانسانية والاجتماعية, 2024)
ﺤﺎوﻟت اﻟدارﺴﺔ اﻟﺤﺎﻟﯿﺔ اﻟﻛﺸف ﻋﻠﻰ ﻤﺴﺘوى ﻛل ﻤن اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ واﻟﻨرﺠﺴﯿﺔ واﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس، ﺒﺎﻹﻀﺎﻓﺔ إﻟﻰ اﻟﺴﻌﻲ ﻟﻤﻌرﻓﺔ أي ﻤن أﺒﻌﺎد اﻟﻛﻤﺎﻟﯿﺔ إﻟﻰ ﺠﺎﻨب ﻤﺤﺎوﻟﺔ اﻟﺘﻌرف ﻋﻠﻰ ﻤدى إﺴﻬﺎم ، اﻟﻌﺼﺎﺒﯿﺔ اﻷﻛﺜر اﻨﺘﺸﺎار ﻟدى أﻓارد ﻋﯿﻨﺔ اﻟدارﺴﺔ اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻓﻲ اﻟﺘﻨﺒؤ ﺒﻨﺸوء اﻟﺸﺨﺼﯿﺘﯿن )اﻟﻨرﺠﺴﯿﺔ- اﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ(، وﺼوﻻ إﻟﻰ اﻟﺒﺤث ﻓﯿﻤﺎ إذا ﻛﺎﻨت ﻫﻨﺎك ﻓروق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ ﻤﺘﻐﯿارت اﻟدارﺴﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر )اﻟﺠﻨس- واﻟﺘرﺘﯿب اﻟﻤﯿﻼدي(، وﻟﺘﺤﻘﯿق أﻏارض اﻟدارﺴﺔ ﺘم اﻻﻋﺘﻤﺎد ﻋﻠﻰ اﻟﻤﻨﻬﺞ اﻟوﺼﻔﻲ اﻟﺘﺤﻠﯿﻠﻲ ﻟﺘﻼؤﻤﻪ وطﺒﯿﻌﺔ ﻤارﻫﻘﺎ ﻤﺘﻤدرﺴﺎ ﻤن ﺒﻌض اﻟﺜﺎﻨوﯿﺎت ﻤن ﺸرق 1200 اﻟدارﺴﺔ، ﺤﯿث ﺘم اﻟﺘطﺒﯿق ﻋﻠﻰ ﻋﯿﻨﺔ ﻗواﻤﻬﺎ وﻏرب وﺸﻤﺎل وﺠﻨوب اﻟﺒﻼد، ﻤﺴﺘﺨدﻤﯿن ﻓﻲ ذﻟك ﻤﻘﯿﺎس اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻟداﻟﯿﺎ ﯿﺴرى ﯿﺤﯿﻰ (Narcissistic Personality وﻤﻘﯿﺎس ﻗﺎﺌﻤﺔ اﻟﺸﺨﺼﯿﺔ اﻟﻨرﺠﺴﯿﺔ ،(2015) اﻟﺼﺎوى اﻟﺘﻲ ﻗﺎم ﺒﻬﺎ ﻛل ﻤن ﺘوﻤﺎس ﻛوﺒﺎرﯿش، وأﯿن دﯿري، واﻟﯿزﺒﯿث أوﺴﺘﯿن Inventory) (NPI) و ٕ ( واﻟﺘﻲ ﻗﺎم ﺒﺘرﺠﻤﺘﻬﺎ Deary, Kubarych & Austin, 2004) اﻋدادﻫﺎ ﻟﻠﻐﺔ اﻟﻌرﺒﯿﺔ اﻟﻌﺎﺴﻤﻲ (، ﺒﺎﻹﻀﺎﻓﺔ إﻟﻰ ﻤﻘﯿﺎس اﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﻟرﺸدي ﻋﻠﻲ اﻟﺠﺎف ودﯿﺎري ﻤﺤﻤد وﻟﻲ ﻋﻠﻲ 2013) ( اﻟذي ﺘم ﺒﻨﺎؤﻩ وﻓق ﻤﻌﺎﯿﯿر 2010) (ﺒﺴﺒب ﻛﻔﺎءﺘﻬﺎ اﻟﻤﺜﺒﺘﺔ DSM-IV-TR) ً ﻋﻠﻤﯿﺎ ﻓﻲ ﺘﺸﺨﯿص وﻗد أﺴﻔرت ﻨﺘﺎﺌﺞ اﻟدارﺴﺔ ﻋﻠﻰ ﻤﺎ ﯿﻠﻲ: ، ﻫذا اﻻﻀطارب - وﺠود ﻤﺴﺘوى ﻤﺘوﺴط ﻤن اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس. 1 - وﺠود ﻤﺴﺘوى ﻤرﺘﻔﻊ ﻤن اﻟﻨرﺠﺴﯿﺔ ﻟدى أﻓارد ﻋﯿﻨﺔ اﻟدارﺴﺔ. 2 - وﺠود ﻤﺴﺘوى ﻤرﺘﻔﻊ ﻤن اﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﻟدى أﻓارد ﻋﯿﻨﺔ اﻟدارﺴﺔ. 3 - اﻷﻓﻛﺎر اﻟﻼﻋﻘﻼﻨﯿﺔ اﻟﻤﺼﺎﺤﺒﺔ ﻟﻠﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻫﻲ أﻛﺜر اﻷﺒﻌﺎد اﻨﺘﺸﺎار ﻟدى أﻓارد ﻋﯿﻨﺔ 4 اﻟدارﺴﺔ. - ﯿﻤﻛن اﻟﺘﻨﺒؤ ﺒﺎﻟﻨرﺠﺴﯿﺔ ﻤن ﺨﻼل اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس. 5 - ﯿﻤﻛن اﻟﺘﻨﺒؤ ﺒﺎﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﻤن ﺨﻼل اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس. 6 - ﻋدم وﺠود ﻓروق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر اﻟﺠﻨس ﻟدى أﻓارد 7 ﻋﯿﻨﺔ اﻟدارﺴﺔ. - وﺠود ﻓروق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ اﻟﻨرﺠﺴﯿﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر اﻟﺠﻨس ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس 8 ﻟﺼﺎﻟﺢ اﻹﻨﺎث. - وﺠود ﻓر وق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ اﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر اﻟﺠﻨس ﻟدى اﻟﻤارﻫق 9 اﻟﻤﺘﻤدرس ﻟﺼﺎﻟﺢ اﻹﻨﺎث. - ﻋدم وﺠود ﻓروق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ اﻟﻛﻤﺎﻟﯿﺔ اﻟﻌﺼﺎﺒﯿﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر اﻟﺘرﺘﯿب اﻟﻤﯿﻼدي 10 ﻟدى ﻋﯿﻨﺔ اﻟدارﺴﺔ. - ﻋدم وﺠود ﻓروق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ اﻟﻨرﺠﺴﯿﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر اﻟﺘرﺘﯿب اﻟﻤﯿﻼدي ﻟدى 11 اﻟﻤارﻫق اﻟﻤﺘﻤدرس. - ﻋدم وﺠود ﻓروق ذات دﻻﻟﺔ إﺤﺼﺎﺌﯿﺔ ﻓﻲ اﻟوﺴواﺴﯿﺔ اﻟﻘﻬرﯿﺔ ﺘﺒﻌﺎ ﻟﻤﺘﻐﯿر اﻟﺘرﺘﯿب اﻟﻤﯿﻼدي 12 ﻟدى اﻟﻤارﻫق اﻟﻤﺘﻤدرس. Abstract: The current study attempted by identifing the levels of neurotic perfectionism, narcissism, and obsessive-compulsive disorder in schoolgoing adolescents. The study sought to determine the most prevalent dimensions of neurotic perfectionism among the study sample, and to investigae the contribution of neurotic perfectionism in predicting the emergence of narcissistic and obsessive-compulsive personalities.It examined whether there were statistically significant differences in the study variables based on gender and birth order.Thus,to achieve the study's objectives, a descriptive analytical approach was adopted due to its suitability and the nature of the studywhich was conducted on a sample of 1200 school-going adolescents from secondary schools in different regions (East, West, North, and South) of the country. For data collection, the studywasbasedon the Neurotic Perfectionism Scale developed by Dalia Yousry El-Sawi (2015), the Narcissistic Personality Inventory (NPI) developed by Thomas Kubarych, Wayne Deary, and Elizabeth Austin (Deary, Kubarych & Austin, 2004) translated and adapted by Al-Asimi (2013), as well as the Obsessive-Compulsive Scale developed by Rashdi Ali Al-Jaaf and Diyari Mohammed Walid Ali (2010) based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR), given its established scientific validity in diagnosing this disorder. The study yielded the following results: • School-going adolescents exhibit a moderate level of neurotic perfectionism. • The study sample shows a high level of narcissism. • The study sample shows a high level of obsessive-compulsive disorder. • The irrational thoughts associated with neurotic perfectionism are the most prevalent dimensions among the study sample. • Narcissism can be predicted based on neurotic perfectionism in schoolgoing adolescents. • Obsessive-compulsive disorder can be predicted based on neurotic perfectionism in school-going adolescents. • There were no statistically significant differences in neurotic perfectionism based on gender among the study sample. • There were statistically significant differences in narcissism based on gender among school-going adolescents, favoring females. • There were statistically significant differences in obsessive-compulsive disorder based on gender among school-going adolescents, favoring females. • There were no statistically significant differences in neurotic perfectionism based on birth order among the study sample. • There were no statistically significant differences in narcissism based on birth order among school-going adolescents. • There were no statistically significant differences in obsessive-compulsive disorder based on birth order among school-going adolescents.
)دارﺴﺔ وﺼﻔﯿﺔ ﻓﻲ ﺒﻌض ﺜﺎﻨوﯿﺎت اﻟوطن: ﺸرق - ﻏرب - ﺸﻤﺎل - ﺠﻨوب(
Keywords: الكمالية العصابية; النرجسية و; المراهق المتمدرس